An Investigation Into the Upgrading Process of Lignin Model Dimer—Phenethyl Phenyl Ether by in situ2H NMR and GC-MS - Yang, Yunyi; Wu, Zhihong; Luo, Ying; Han, Guangting; Jiang, Wei; Wang, Maorong; Ben, Haoxi (Frontiers in Energy Research, 2020)
A key challenge in studying the upgrading process for the thermochemical conversion of biomass, such as lignin, is to understand the underlying mechanisms of catalytic conversion at the atomic scale. In this study, a method combined with in situ 2H NMR and GC-MS was proposed for investigating the conversion of phenethyl phenyl ether (PPE) in the hydrotreating process, as catalyzed by Pd, Ru, and Pt loaded onto C or γ-Al2O3. The results indicated that Pd/γ-Al2O3 prefers to produce more ether bond-cleaved products, while Pt prefers to produce more hydrogenation products from PPE. Furthermore, based on this new strategy, a possible reaction mechanism of PPE with Pd/γ-Al2O3 was presented from the atomic point of view, showing the potential of this in situ detection method for reaction mechanism studies. Besides, mechanistic investigations by GC-MS were accomplished for the hydrothermal treatment of PPE for comparison with the new method. The results showed that the in situ 2H NMR combined with GC-MS provided a deeper understanding of the catalytic mechanism compared to GC-MS alone.